CLASSIFICATION AND CLUSTERING - Axmedov Baxriddin Madaminovich; Astonaqulova Kibriyoxon Baxriddin qizi (Web of Journals Publishing, 2024)
This article provides information about classification and clustering methods, classification and clustering algorithms, their workflow and application in real life, as well as examples.
Keywords: Interface, artificial intelligence, computer, classes, classification, clustering, credit, risk, big data, categorized, unclassified